REALISASI INVESTASI JEPANG MELALUI JAPAN INTERNATIONAL COOPERATION AGENCY (JICA) DI INDONESIA TERKAIT PEMBANGUNAN MRT JAKARTA - Farid, Reynaldi; Fuadi, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study focuses on Japanese investment efforts in the transportation infrastructure sector in Indonesia, one of which is the construction of the Mass Rapid Transit (MRT). After the defeat of Japan in the seizure of the Jakarta-Bandung high-speed train contract by China in 2015, the railway sector became a prestigious project and made the rivalry between Japan and China in the struggle for various infrastructure projects in Indonesia even stronger. However, Japan has actually secured several railway projects such as the Jakarta-Surabaya Semi-fast Train and MRT Jakarta Phases 1 and 2.This study aims to find out how Japan's steps in realizing its investment in the construction of the Jakarta MRT. This research is analyzed through the perspective of liberalism which is studied more deeply using the theory of international cooperation and the level of analysis of the nation state. This study also uses descriptive research methods and secondary research data obtained from data collection techniques by literature study where data comes from official documents, a number of journals and news related to research.The results of this study indicate that the realization of Japanese investment in the construction of the Jakarta MRT in Indonesia, which consists of phase 1 and phase 2. The realization of this development investment can take place quite optimally, with several indicators such as phase 1 which has been operating and phase 2 which is under construction, the funding process is transparent and brings positive impacts such as employment, increased mobility and also has an impact on the environment. Keywords: JICA, Investment, Infrastructure, Transportation, MRT.